Fully developed mixed convection flow in a vertical channel with electrokinetic effects: Exact solution. Issue 5 (6th December 2018) - Jha, Basant Kumar; Oni, Michael O.
Abstract : Purpose: The purpose of this paper is to investigate electrokinetic and mixed convection (pressure gradient and buoyancy) effects on reverse flow formation at the channel walls. Design/methodology/approach: The electrical potential distribution was modelled using the Poisson–Boltzmann equation while the governing momentum and energy equations are modelled from the Navier–Stokes equations and solved exactly. Findings: It is found that flow reversal at the walls is enhanced by electrokinetic parameter whereas increasing degree of asymmetric parameter up to symmetric heating eliminates reverse flow formation at the walls no matter the electric charge distribution. Originality/value: The results of this paper indicate that degree of asymmetric heating, mixed convection parameter and electrokinetic parameter regulate fluid velocity, rate of heat transfer, skin friction and reverse flow formation at the walls.